Beyond the wound and oblivion: the voz memoriosa and its narrative in two Radio Ucamara documentaries - García, Andrea Cabel (2022)
In this research, we use an interdisciplinary approach to analyze the narrative of Radio Ucamara in order to render visible the material and spiritual consequences of the largest oil spill of the first decade of the 2000s in Peru. To do so, I analyze two documentaries: Consuelen a mi pueblo. Cuninico, dos años después (14' 37"), and Daños a la espiritualidad kukama (11' 40"). They show their forms of resistance and denunciation through what we call a voz memoriosa. This conceptual metaphor is characterized by intersecting their own social practices (songs, icaros, and stories) with official narratives (the chronology of the spill, the tallying of material damage, and extracts from trials). Thus, their way of presenting the consequences of the spill and of representing themselves in relation to them is not only cross-cultural, but also highly metaphorical. I chose to apply a qualitative approach based on ten extensive, in-depth, semi-structured telephone interviews and by instant messaging with Leonardo Tello, director of Radio Ucamara, from May 2020 to June 2021. The analysis and the theoretical concept reveal that documentaries are part of their social practices insofar as they involve community members and the non-human subjectivities with whom they relate. Thus, they, on their own terms, manage to interweave Western perspectives of linear (cause-consequence) remembrance with their polyphonic remembrance of organic aesthetics. The concept that I propose allows us to broaden Ginsburg’s use and understanding of organic aesthetics. The study also offers an analysis of the way in which those affected describe the consequences that environmental pollution brings directly upon their spirituality.